Pengaruh Customer Relationship Management Terhadap Loyalitas Konsumen MS Glow Jember - Sukma Hadi, Nadia (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
With increasingly modern developments, many innovations in cosmetic production have emerged in the business world. MS Glow has a high market valuation even though the price offered is quite expensive.. Keeping consumers loyal to the product can be a solution to competition. The influence of trust, commitment, communication, and problem handling on the level of customer loyalty of MS Glow in Jember is examined in this study. The research technique carried out on the object of MS Glow in Jember is based on quantitative research methods. Quantitative data used in this study were obtained through questionnaires, documentation, and interviews. The main population of this study were consumers who had made purchases at MS Glow Jember. This study used non-probability incidental sampling techniques, using 160 MS Glow customers in Jember as samples. Respondents' responses were measured using a Likert scale. The data was processed through multiple regression analysis conducted using the SPSS program. The results showed that trust affects customer loyalty, commitment affects customer loyalty, communication affects customer loyalty, and problem solving affects MS Glow customer loyalty. All variables that measure customer relationship management in this study affect MS Glow consumer loyalty in Jember. Thus it can be concluded that customer relationship management is effective and able to increase consumer loyalty. The results of this study confirm all the proposed hypotheses